KESALAHAN BUNYI SOKUON DAN CHOO’ON OLEH SISWA XII TATA BOGA SMK NEGERI 1 BAWEN - Sovia Andriani; Rosalina Wahyu Riani (Universitas Ngudi Waluyo, 2025)
Character is an important element in fictional work besides the other elements. In fiction, character reveals a textual representation of human being, or occasionally another creature. Character is the player in the story and it makes the story alive. Every character in a story has characterization. Characterization is the process of conveying information about characters in fiction. In other words, characterization is the way an author describes their characters’ characteristic in the story. This research was motivated by students of class XII Culinary Art at SMK Negeri 1 Bawen who still read simple Japanese sentences without caring about the difference in sound between sokuon and choo'on. This study aims to determine the errors in the sound of sokuon and choo'on and the factors that influence them. The method used in this study is descriptive qualitative by collecting data using note-taking techniques, interview techniques, recording techniques and research sources from Nihongo Kira-Kira 1 book chapter 3, chapter 7 and chapter 9 and collecting samples using simple random sampling. The sokuon and choo'on errors can be found when reading simple Japanese sentences. The results of this study found that there were mistakes and errors that were influenced by internal and external factor from students of Class XII Culinary Art, causing errors in the sound of sokuon and choo'on. Suggestions for further research can explore more data, methods or samples and this research can be studied from other branches of linguistics.